Pengembangan Teknologi Pengemasan Untuk Meningkatkan Daya Saing Produk Olahan Berbasis Bahan Baku Daging Dan Jamur Tiram Di Desa Watu Kec. Marioriwawo, Kab. Soppeng, Sulawesi Selatan - Muhammad Irfan Said; Renny Fatmyah Utamy; Sutomo Syawal; Miah Said (Universitas Mataram, 2025)
One of the main challenges faced by partners is their limited knowledge regarding product packaging, particularly for processed meat and oyster mushroom-based chips. The objective of this activity was to improve partners' capacity and skills in selecting packaging types and carrying out product packaging processes, both for processed meat and chips. The activity was conducted in Watu Village, Marioriwawo District, Soppeng Regency, South Sulawesi. The partners involved were the